Knowledge gaps in food allergy among the general public in Jeddah, Saudi Arabia: Insights based on the Chicago food allergy research survey - Takrouni, Abdulrahman Ahmad; Omer, Ibrahim; Alasmari, Faisal; Islamuldeen, Suhayb; Ghazzawi, Amr Yasser; Zahrani, Mohammed Ibrahim; Ahmed, Mohamed Eldigire; Abushouk, Amir (Frontiers in Allergy, 2022)
Background Food allergy is an increasing health concern. Studies have shown that food allergy knowledge is lacking among people, especially in areas related to distinction between food allergy and intolerance, symptoms recognition, and current means of management. This knowledge gap puts allergic patients at more risk of getting fatal anaphylactic reactions, which occur mostly in public areas. Locally, Public's knowledge and attitudes of food allergy was not sufficiently investigated. Therefore, we aim to assess food allergy knowledge and attitudes among Jeddah population in Saudi Arabia. Methods We adopted The Chicago Food Allergy Research Survey for the General Public (CFARS-GP) and used it as a data collection tool. We hosted the questionnaire on Google Forms and distributed the link through social media outlets targeting individuals of Jeddah population who are 18 years old and above. Results A total of 510 individuals completed the survey. The respondents answered 56% of the knowledge-based items correctly. Knowledge was strongest in symptoms/severity and definition/diagnosis, while it was weakest in susceptibility and prevalence, distinction between food allergy and intolerance, and food allergy management. Higher knowledge was significantly associated with prior training in food allergy, food-allergic acquaintance (i.e., having food allergy or knowing an allergic patient), and being a relative of a health care worker. For the attitudes, respondents thought that food allergy negatively affects patients' quality of life, and that schools should establish policies to protect allergic children; however, they downplayed stigma associated with food allergy. Conclusion Increased food allergy knowledge among the general public is needed especially in areas related to susceptibility and prevalence, distinction between food allergy and intolerance, triggers and environmental risks, and the management of food allergy. Prior experience with food allergy through (1) training, (2) food-allergic acquaintance, or (3) being a relative of a health care worker increases food allergy knowledge significantly. Thus, targeted educational interventions might have a significant effect in improving food allergy knowledge among the general population.